Analisis Faktor yang Mempengaruhi Kinerja Jaringan Komputer dalam Lingkungan Multi-User - Fitrian, Harry Pribadi; Difa, Damia Hasna; Vina Aulia Melianti; Fajar Muhammad Ramdhani (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
This study addresses the degradation of computer network performance in multi-user environments due to high traffic loads, limited bandwidth, and suboptimal configurations, leading to reduced throughput, increased delay, jitter, and packet loss. The objective is to identify key influencing factors and effective optimization techniques through a Systematic Literature Review (SLR) of empirical studies from 2020-2025. The methodology involved searching databases like Google Scholar and Garuda using keywords such as "network performance," "QoS," and "multi-user," selecting 7 relevant articles from 200 initial results via inclusion/exclusion criteria based on title, abstract, and full-text relevance. Findings reveal that Quality of Service (QoS) implementation significantly mitigates issues, reducing jitter by up to 40%, packet loss below 0.1%, and stabilizing real-time services like VoIP in settings such as schools, offices, and internet cafes.